d–d Dative Bonding Between Iron and the Alkaline-Earth Metals Calcium, Strontium, and Barium - Stegner, Philipp; Färber, Christian; Oetzel, Jan; Siemeling, Ulrich; Wiesinger, Michael; Langer, Jens; Pan, Sudip; Holzmann, Nicole; Frenking, Gernot; Albold, Uta; Sarkar, Biprajit; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Double deprotonation of the diamine 1,1′-(tBuCH2NH)-ferrocene (1-H2) by alkaline-earth (Ae) or EuII metal reagents gave the complexes 1-Ae (Ae=Mg, Ca, Sr, Ba) and 1-Eu. 1-Mg crystallized as a monomer while the heavier complexes crystallized as dimers. The Fe⋅⋅⋅Mg distance in 1-Mg is too long for a bonding interaction, but short Fe⋅⋅⋅Ae distances in 1-Ca, 1-Sr, and 1-Ba clearly support intramolecular Fe⋅⋅⋅Ae bonding. Further evidence for interactions is provided by a tilting of the Cp rings and the related 1H NMR chemical-shift difference between the Cp α and β protons. While electrochemical studies are complicated by complex decomposition, UV/Vis spectral features of the complexes support Fe→Ae dative bonding. A comprehensive bonding analysis of all 1-Ae complexes shows that the heavier species 1-Ca, 1-Sr, and 1-Ba possess genuine Fe→Ae bonds which involve vacant d-orbitals of the alkaline-earth atoms and partially filled d-orbitals on Fe. In 1-Mg, a weak Fe→Mg donation into vacant p-orbitals of the Mg atom is observed.
CRIS-Team Scopus Importer:2020-07-10
Keywords: alkaline-earth metals; ferrocene; metal–metal bonding; theoretical chemistry